If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 37 = 15x + -66 Reorder the terms: 37 + 6x = 15x + -66 Reorder the terms: 37 + 6x = -66 + 15x Solving 37 + 6x = -66 + 15x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15x' to each side of the equation. 37 + 6x + -15x = -66 + 15x + -15x Combine like terms: 6x + -15x = -9x 37 + -9x = -66 + 15x + -15x Combine like terms: 15x + -15x = 0 37 + -9x = -66 + 0 37 + -9x = -66 Add '-37' to each side of the equation. 37 + -37 + -9x = -66 + -37 Combine like terms: 37 + -37 = 0 0 + -9x = -66 + -37 -9x = -66 + -37 Combine like terms: -66 + -37 = -103 -9x = -103 Divide each side by '-9'. x = 11.44444444 Simplifying x = 11.44444444
| 9pt+2t-2p+3t= | | -5.6n=40 | | 12x-7x= | | q+12-2(q-22)=-q+56 | | (7-3i)-(-9+5i)=0 | | -5.6=40 | | 70-4x=5x+23 | | h/5=-12 | | 20+.5w=w | | (p-6)(p+4)= | | 10z=4-11z | | -74x=47 | | 20+.5=x | | 4d+5.73=12.57 | | 2+5m=52 | | -40+2X=y | | -5(4y-10)+3(3y+6)= | | 127-10x=8x+17 | | -1.6b=3 | | 3(x+2)=6(x-3) | | -(x-8)=18 | | .08(x+7)=.04(2x+8)+.24 | | .08(x+7)=.04(2x+9)+.24 | | 4x+x+7=10x-5x+7 | | 6-2f=2.2 | | 7-m=-2 | | y=-40+2x | | 1+6x-5=3x-16 | | -6.09=-0.49+-2h | | (3+2i)+(7-6i)=0 | | 4c+7=4c+7 | | -12(x+2)=-14x-24 |